Penghijauan Berbasis Edukasi: Peran Masyarakat dalam Gerakan Penanaman Pohon di Lingkungan Kelurahan Pabuaran - Sari, Novita; Salangi, Franciscus Guman; Anisa, Anisa; Alifya, Kembang; Puji Astuti, Lili Koesneti; Adila, Puja Putri; Sari, Meli Lupita; Mohamad Tito, Naufal Dzaky; Dwiyanti, Elsa; Sahni, Anna Jannatu (Universitas Pahlawan Tuanku Tambusai, 2025)
Environmental problems in urban areas are increasing due to the reduction of green open spaces and low public awareness of environmental sustainability. One possible solution is through an education-based greening movement that involves active community participation. This Community Service Program (PKM) aims to increase ecological awareness, technical skills, and participation of Pabuaran Village residents in tree planting and maintenance activities. The method used is Participatory Action Research (PAR), which includes outreach, technical training, tree planting, mentoring, and evaluation. The activity results showed a significant increase in community understanding of the function of trees, from 38% before the activity to 85% after the education. A total of 150 fruit and shade tree seedlings were successfully planted at various strategic locations, with a 95% survival rate in the first week. Community participation is also reflected in active involvement in the planting activity and the formation of environmental awareness groups to support the program's sustainability. In addition to its ecological impact, this activity also strengthens social solidarity among residents through the practice of mutual cooperation. Education-based greening has proven effective as a strategy for strengthening ecological awareness and community empowerment.